1998
DOI: 10.3109/10837459809028638
|View full text |Cite
|
Sign up to set email alerts
|

Solubility Properties of Racemic Praziquantel and Its Enantiomers

Abstract: The purpose of this study was to characterize the solubility and thermodynamic properties of the optical isomers of the anti-schistosomal drug, praziquantel (PZQ) and to compare these properties to those of the racemic product used in commercial preparations (Biltricide, generic drugs). The crystalline enantiomers of PZQ exhibited different thermal properties than the racemic drug. The melting points and the enthalpies of fusion obtained from the differential scanning calorimetry (DSC) scans were nearly identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 8 publications
4
29
0
Order By: Relevance
“…The S-PZQ plasma concentration values were always larger than the R-PZQ ones in the first 3 months with the R-PZQ/S-PZQ ratios decreasing from 0.72 to 0.28 over this time, which was similar to the serum ratios (range: 0.54 to 0.33) previously measured in five healthy Caucasian volunteers by Westhoff et al [ 44 ]. These results confirm that PZQ enantiomers are subject to selective metabolism similar to the enantio-selective activity noted against the adult schistosome worm [ 32 36 ]. The initial average AUC and C max value of S-PZQ in plasma were higher than that of R-PZQ by 79.2% ( P < 0.01) and 114.0% ( P < 0.05), respectively, which meant that the AUC R/S ratio of dogs was 0.56, while this ratio was 0.39 in a healthy volunteer [ 45 ].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The S-PZQ plasma concentration values were always larger than the R-PZQ ones in the first 3 months with the R-PZQ/S-PZQ ratios decreasing from 0.72 to 0.28 over this time, which was similar to the serum ratios (range: 0.54 to 0.33) previously measured in five healthy Caucasian volunteers by Westhoff et al [ 44 ]. These results confirm that PZQ enantiomers are subject to selective metabolism similar to the enantio-selective activity noted against the adult schistosome worm [ 32 36 ]. The initial average AUC and C max value of S-PZQ in plasma were higher than that of R-PZQ by 79.2% ( P < 0.01) and 114.0% ( P < 0.05), respectively, which meant that the AUC R/S ratio of dogs was 0.56, while this ratio was 0.39 in a healthy volunteer [ 45 ].…”
Section: Discussionsupporting
confidence: 80%
“…PZQ is a racemic mixture of two enantiomers, R-(−)-praziquantel (R-PZQ) and S-(+)-praziquantel (S-PZQ) [ 31 , 32 ], the former being the main effector with the latter and its metabolites not having significant antiparasitic properties [ 33 38 ]. While the comparatively high price of producing pure R-PZQ limits its application in practice, there are enantio-selective, metabolic pathways with regard to R-PZQ and S-PZQ that could be useful in a future scenario [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed that only the enantiomer R has therapeutic value, with the S enantiomer being only responsible for the bad taste associated with the drug. (Meyer et al, 2009) Although the WHO and the Center for Disease Control (CDC) consider PZQ an effective, safe and lowcost drug, (CDC,12); (WHO,16b) this is far from being a perfect drug, mainly because of its low solubility in water (only 0.04 g/100 mL)(de la Torre et al, 1999); (El-Arini et al, 1998) and a first pass effect (Lindenberg et al, 2004) that compromises its bioavailability. In fact, PZQ is classified in the Biopharmaceutical Classification System (BCS) as a type II drug (poorly soluble, highly permeable).…”
Section: Fig1 Herementioning
confidence: 99%
“…And indeed it has been demonstrated that an increase in the amount of PVP increases PZQ solubility and that physical mixtures and solid dispersions behave differently in terms of solubility and dissolution rates. (El-Arini et al, 1998) Furthermore, amorphous PZQ inclusion in the PVP matrix has been demonstrated by scanning electron microscopy (SEM) and X-ray powder diffraction (DRX). (de la Torre et al, 1999) The development of amorphous solid dispersions is of great interest, so it is crucial to find suitable techniques to characterize them in terms of drug degradation, crystallinity of the active principle, drug-carrier miscibility and intermolecular interactions.…”
Section: Fig1 Herementioning
confidence: 99%
“…It also possesses low aqueous solubility (C S =0.4 mg/mL) (25,26) and erratic absorption from the gastrointestinal tract. It is, therefore, classified as a BCS Class II drug (8,9).…”
Section: Effect Of CD Complexation On the Solubility/dose Ratio Of Pzqmentioning
confidence: 99%